The Analysis of Triple Bottom Line Approach on Firm Performance Level Assessment - Kurniawati, Dwi Indri; Zuhroh, Diana; Setiyorini, Wahyu; Mennita, Ria (Proceedings of International Conference of Graduate School on Sustainability, 2022)
The historical background of bookkeeping improvement developed rapidly when the modern transformation in England (1760-1860), made the details of bookkeeping more and more involving the responsibility to the owners of capital, bringing a promising direction of the company for the owners. Companies that support capital owners exploit normal assets and social networks in a wild manner, causing damage to natural habitats and ultimately disrupting the existence of the population. Analyzing the influence of corporate social responsibility, good corporate governance, and good corporate governance moderating the relationship of corporate social responsibility on firm value. The data collection method uses documentation and the type of data in this study uses secondary data. The research sample is a manufacturing company listed on the IDX for 2014-2018. The analytical method used there are 3 test methods, namely the classical assumption test, heteroscedasticity, and normality test. From the results of the research that has been carried out, it is found that the CSR variable fundamentally has an influence on company value, the GCG variable has an influence on company value, and the GCG variable maintains the CSR relationship, which fundamentally affects the company value. The research conducted, has limitations that are considered for subsequent analysis to obtain the best results. CSR as an autonomous variable in its impact on firm value, The company makes a test of only 100 assembled companies, Emotional influence in the company’s valuation Keywords: Corporate Social Responsibility, Corporate Values, Corporate Governance, Managerial Moderation